520PA phase II study to evaluate abscopal effect by palliative radiation therapy in nivolumab treatment for pretreated non-small cell lung cancer (HANSHIN 0116). (24th November 2019) - Hata, A; Satouchi, M; Morita, S; Ota, Y; Urata, Y; Kawa, Y; Okada, H; Mayahara, H; Kokubo, M; Akazawa, Y; Uenami, T; Tamiya, M; et al.
Abstract: Background: While immune checkpoint inhibitors (ICIs) have been shown to be effective for non-small cell lung cancer (NSCLC), their monotherapeutic response rate (RR) is roughly 20%. It has been noted that local radiation therapy (RT) might potentially activate off-target antitumor effect, which is so called "abscopal effect" induced by immune-mediated mechanism. We evaluated whether palliative-RT induced abscopal effect, resulting in improvement of Nivolumab (Nivo) effectiveness. Methods: Pretreated advanced NSCLC patients (pts) who were indicated for Nivo and scheduled for palliative-RT were started on RT within 10 days of administration of Nivo 3 mg/kg q2 weeks until attached document was revised to 240 mg/body q2 weeks. The primary endpoint was RR of non-irradiated tumor lesions. Results: Twenty-eight pts were enrolled from May 2016 to January 2019. The study was terminated before completion of targeted initial sample size (n = 35), because of poor accrual. The median age was 67 years (range: 53-89). 15 pts were male. 21 pts had adenocarcinoma histology, 2 pts squamous histology, and 6 pts driver oncogene alterations. 25 pts were PS0/1, and 3 pts PS2. 14 pts were treated as 2nd-line, 2 pts as 3rd-line, and 12 pts as 4th-line or later. The median number of treatment cycles was 4 (range: 1-6). Median radiation dose was 30 Gy (range: 25-40), and 16 pts were irradiated on the bone, 5 pts on the adrenal grand, and 2 pts on the primary lesion. The objective RR of non-irradiated tumor lesions was 14.3% (95% CI: 1.3–27.2). Partial response (PR) was observed in 3 pts treated as 2nd-line (3/14, 21.4%), and 1 pt as 3rd-line (1/2, 50%). No PR was observed in pts treated as 4th-line or later (0/12, 0%). The median PFS was 2.7 months (95% CI: 1.0–3.5). No severe and specific adverse events (AEs) of Nivo in combination with RT were observed compared to historical data of Nivo monotherapy. Conclusions: Although the sample size was small, cleared abscopal effect by palliative-RT was not observed in Nivo treatment. However, some pts well responded to Nivo with palliative-RT during early-lines of treatment (2nd/3rd-line). Further investigations in the early-lines are warranted to evaluate a substantial synergistic effect of RT with ICIs. Clinical trial identification: UMIN000023646. Legal entity responsible for the study: HANSHIN Oncology Group. Funding: ONO Pharmaceutical Company. Disclosure: A. Hata: Speaker Bureau / Expert testimony, Research grant / Funding (institution): Boehringer Ingelheim; Speaker Bureau / Expert testimony, Research grant / Funding (institution): Eli Lilly; Speaker Bureau / Expert testimony, Research grant / Funding (institution): AstraZeneca; Speaker Bureau / Expert testimony: Chugai; Research grant / Funding (institution): MSD. M. Satouchi: Speaker Bureau / Expert testimony, Research grant / Funding (institution): AstraZeneca; Speaker Bureau / Expert testimony, Research grant / Funding (institution): Boehringer Ingelheim; Speaker Bureau / Expert testimony, Research grant / Funding (institution): BMS; Speaker Bureau / Expert testimony, Research grant / Funding (institution): Chugai; Speaker Bureau / Expert testimony, Research grant / Funding (institution): Eli Lilly; Speaker Bureau / Expert testimony, Research grant / Funding (institution): MSD; Speaker Bureau / Expert testimony, Research grant / Funding (institution): Novartis; Speaker Bureau / Expert testimony, Research grant / Funding (institution): ONO; Speaker Bureau / Expert testimony, Research grant / Funding (institution): Pfizer; Research grant / Funding (institution): Takeda; Speaker Bureau / Expert testimony: Taiho. D. Harada: Honoraria (self): ONO; Honoraria (self): BMS. All other authors have declared no conflicts of interest.